A REPORT ABOUT COMPETITION OF PROFESSIONAL MASTERSHIP «THE BEST WORK IN PROSTHETIC DENTISTRY» 2016 - S. Zholudev E.; С. Жолудев Е. (The actual problems in dentistry, 2016)
In the article, in the genre of reportage, man talks about the specifics of the final of competition of professional mastership «the best work in prosthetic dentistry». This year the event took place on 20‑21 October in the city of Arkhangelsk, on the territory of the «Northern State Medical University» of the Ministry of Health of Russia. At the same time with the competition there was held the «II Arctic Dental Forum». Among the participants of this event were members of the jury, who had 30 minutes to read their lectures. Reports of the members of the jury were devoted to implantology and digital technologies. The head the jury was traditionally the honored worker of science, M. D., professor Lebedenco I. Y. – head of the department of materials science CSIIS & JFS RF. The jury consisted of 9 people, among whom were leading professors of the Russian Federation in the field of prosthetic dentistry, textbook authors, as well as the President of StAR, director of NIIAMS – Ph. D. Sadowski V. V. In the final of competition 7 dentists were admitted. Contestants in two days completed 13 tasks and publicly defended the results of treating of a patient with a partial or total loss of teeth with implants and digital technologies. The most successful in competitive tasks was a participant from Ekaterinburg – Ph. D. Zholudev DS, and received the title of «Champion of Russia 2016 in professional skills for prosthetic dentistry contest». В статье, в жанре репортажа, рассказывается об особенностях прохождения финала конкурса профессионального мастерства «Лучшая работа по ортопедической стоматологии» в 2016 году. В этом году данное мероприятие проходило 20‑21 октября в городе Архангельске, на базе ФГБОУ ВО «Северный государственный медицинский университет» Минздрава РФ. Параллельно конкурсу проходил «II Арктический стоматологический форум». Среди участников данного мероприятия – члены профессионального жюри, которым для прочтения лекции выделялось до 30 мин. Доклады членов жюри были посвящены вопросам имплантологии и цифровых технологий. Возглавлял жюри традиционно Заслуженный деятель науки РФ, д.м.н., профессор Лебеденко И. Ю. – зав. отделом материаловедения ФГБОУ ВО «ЦНИИС и ЧЛХ» МЗ РФ. В составе жюри, которое состояло из 9 человек, были ведущие профессора РФ в области ортопедической стоматологии, авторы учебников, а также Президент СтАР, директор НИИАМС – к.м.н. В. В. Садовский. В финал конкурса было допущено 7 человек. Конкурсанты за два дня выполнили 13 заданий и публично защитили результаты лечения пациента с частичной или полной потерей зубов с использованием имплантатов и цифровых технологий. Наиболее успешно справился с конкурсными заданиями участник из Екатеринбурга – к.м.н. Жолудев Д. С., получивший звание «Чемпион России 2016 года в конкурсе профессионального мастерства по ортопедической стоматологии».